Magnetic Nanomaterials in Chinese Medicine Chemical Composition Analysis and Drug Metabolism and Its Industry Prospect and Development Path Research - Tengfei Ma; Peng Liu (Journal of Chemistry)
The paramagnetism and superparamagnetism of magnetic nanomaterials are very important for in vivo applications. The magnetic particles with paramagnetism or superparamagnetism can redistribute the magnetic particles after the magnetic field is withdrawn, which is widely used for the separation and purification of biomolecules. At the same time, superparamagnetic particles can also be used as MRI imaging contrast agent. Compared with Western medicine, traditional Chinese medicine is different from Western medicine in that it is originated from nature and has thousands of years of clinical efficacy. Therefore, we hope to elaborate the complex mechanism of traditional Chinese medicine through some modern technical means: through the establishment of relevant quality control system, Chinese medicine will be recognized and popularized in the international field. Therefore, this paper discusses the application of magnetic nanomaterials in the chemical composition analysis and drug metabolism of traditional Chinese medicine and its industrial prospect and development path. Firstly, the advantages of magnetic nanomaterials and the shortcomings of chemical composition analysis technology of traditional Chinese medicine are analyzed theoretically. Then, through the experimental simulation, the results show that, under the optimal conditions, the magnetic nanomaterials can be used to analyze the chemical composition of traditional Chinese medicine. The peak current and concentration of THP showed a good linear relationship in the range of 5.2 × 10−8 ∼ 2.1 × 10−5  mol/L, and the detection limit was 1.9 × 10−7  mol/L. Moreover, it showed effective results in repeatability, stability, and interference tests. Therefore, magnetic nanomaterials play an important role in the chemical composition analysis and drug metabolism of traditional Chinese medicine as well as its industrial prospect and development path.